Prognostic value of (18)F-FDG PET/CT metabolic parameters in small cell lung cancer - Choi, Eun Kyoung (J Int Med Res, 2019)
OBJECTIVE: To compare the prognostic values of metabolic parameters from pretreatment PET/CT between limited disease (LD) and extensive disease (ED) small cell lung cancer (SCLC) patients. METHODS: Data on 118 newly diagnosed SCLC patients (50 LD and 68 ED) who underwent pretreatment positron emission tomography–computed tomography (PET/CT) were reviewed. For PET, metabolic parameters were measured for: (1) primary tumor, maximum standardized uptake value (SUVmax), metabolic tumor volume, and total lesion glycolysis; and (2) all tumor lesions, SUVmax of the hottest tumor, whole body metabolic tumor volume (WBMTV), and whole body total lesion glycolysis (WBTLG). Prognostic values of metabolic parameters and other clinical variables were analyzed to predict overall survival (OS). RESULTS: In LD, SUVmax of the primary tumor was an independent prognostic factor for OS. Patients with high SUVmax showed significantly worse OS than those with low SUVmax. In ED, WBMTV and WBTLG were independent prognostic factors for OS. Patients with high WBMTV or WBTLG showed significantly worse OS than those with low WBMTV or WBTLG. CONCLUSIONS: SUVmax of primary tumor was the only independent prognostic factor for OS in LD SCLC patients. WBMTV and WBTLG were independent prognostic factors in ED SCLC patients.